SURFACE MODIFICATION OF ALUMINA-SILICA BY ADDITIVE AGENT USING SOL-GEL METHOD AS FILLER DENTAL COMPOSITE - Faza, Yanwar; Takarini, Veni; Febrida, Renny; Karlina, Elin (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2023)
Background: Macro-sized and inhomogeneous distribution of ceramic filer particles make it difficult to obtain smooth surfaces of dental composite after polishing. Objective. This study aims to synthesize alumina silica (Al2O3-SiO2) fillers using sol gel method with the additives agent chitosan 5%, 10% and polyethylene glycol (PEG) 5% to produce micro particle size and evenly distributed particle as filler dental composite. Methods. The type of research is descriptive explorative. The sol-gel process was utilized to synthesize filler particles of Al2O3-SiO2. TEOS was dissolved in ethanol and mixed with acetic acid as catalyts. Al2(NO3)3 was added into the solution and mixed homogenously. Subsequently, the additive agents (Chitosan 5%, chitosan 10% and PEG) were mixed into the mixture for 30 minutes. Drying the samples for 48 hours at 60°C in the oven. The Dynamic light scattering (DLS) SZ-1 was used to evaluate the size, particle distribution and zeta potential. Result. The results showed that the addition of chitosan 10% produced a smaller size of Al2O3-SiO2 compared to other samples. A homogeneous particle distribution is shown in the sample with PEG 5%. Meanwhile, zeta potential values of the filler particles Al2O3-SiO2 with the addition of chitosan 10% shows the biggest value. Conclusion: The additive agent of chitosan 10% can modify the surface of filler Al2O3-SiO2 in order to inhibit particle growth more effectively but better particle distribution is shown in samples with PEG 5% due to the lower viscosity than chitosan thus it is easily homogenized in the solution